The Rise of Cyber-Activism and Digital Disobedience during the Arab Spring Uprisings (London Journal of Research In Humanities and Social Sciences, 2023)
The fomented fulminations of social disarray, rebellious revolts and the outrageous outbursts of scandalously turbulent political turmoil inflamed during the dystopian plight of the Arab spring have been monumental milestones and remarkably watershed moments old-anchored in the Arab political history and its cultural memory. The tragic war casualties, catastrophic disasters, the horrendous butcheries of innocent civilians and collateral damage have been quintessential centerpieces of intense national and international media coverage alike. Hence, amid the chaotically sweeping whirlwind of such insurgent uprisings and insurrectional upheavals, the indispensably fundamental role of digital media, the practical serviceability of New Information Technologies (ICTs) and Cyber-Activism or digital disobedience become thought-provoking areas of extensive research theoretically reconfigured within the contextual contours of cyber-anthropology and digital sociology. Hence, the principal sine qua non of this research paper is to critically re-interrogate and re-investigate in depth the influential contributions of Cyber-activism and digital media of diverse electronic types in filming, recoding and documenting the cataclysmic calamities and the destructive apocalypse of the Arab spring. In so doing, it also aims to perspicuously cast the spotlight on the practical applicability, versatile multi-tasking and significant operations of multimedia platforms, online outlets and social networks in the democratization of the Arab autocratic regimes and their crucial roles in prompting regime transformation through re-appraising their importance in the liberalization of the Arab constitutions.
Keywords: youth media agency; cyber-activism; cyber-anthropology; digital communities; online identities; virtual political mobilization